1978
DOI: 10.1002/app.1978.070220701
|View full text |Cite
|
Sign up to set email alerts
|

A thermomechanical investigation of highly cold‐drawn polycarbonate

Abstract: SynopsisA new technique detecting molecular motions in drawn polymers was applied to highly cold-drawn polycarbonate of bisphenol A. It is shown that the sample exhibits thermal shrinkage in three steps with the temperature increase up to above the glass transition temperature. The molecular relaxation at the highest temperature is due to the glass transition. The other two molecular motions a t the lower temperature are those of main chain in the glassy state and they correspond to the molecular motions as re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1980
1980
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Below we would like to explore in further detail the characteristics of the elastic yielding. We also note that thermal shrinkage of a cold-drawn polymer glass, after unloading from the strain hardening regime, has been known to take place since 1950s. , In our new understanding, such shrinkage is clearly another form of elastic yielding. We will discuss its effect on the elastic yielding in section .…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…Below we would like to explore in further detail the characteristics of the elastic yielding. We also note that thermal shrinkage of a cold-drawn polymer glass, after unloading from the strain hardening regime, has been known to take place since 1950s. , In our new understanding, such shrinkage is clearly another form of elastic yielding. We will discuss its effect on the elastic yielding in section .…”
Section: Resultsmentioning
confidence: 84%
“…Elastic yielding should be a universal phenomenon for all ductile polymer glasses. Apart from PC, 38,45,51 in this work we have also two other ductile glasses: PET 45 and PPE. Since they are ductile at room Figure 9 shows that all of them exhibit the elastic yielding phenomenon.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have presented a new technique detecting molecular motions in solid polymers using thermal contraction under uniform rate of heating. 5,6 One of the two objects of the present article is to show multiple molecular relaxations of highly hot-drawn and quenched poly(methy1 methacrylate) and polycarbonate of bisphenol A. Almost all the molecular relaxations associated with shrinkage are above their glass transition temperatures.…”
Section: Introductionmentioning
confidence: 93%
“…These last experiments on PC demonstrate that the chains have a great mobility even far below T g . Kato and Kambe [33] found that annealing at 140°C (10°C below T g ) permits the complete relaxation of the cold drawn sample. These experiments are not possible for PS; this polymer is fragile and the sample breaks during cold deformation, before yielding.…”
Section: Comparison Between the Various Relaxation Times And The A Anmentioning
confidence: 99%